2022
DOI: 10.1038/s41597-022-01720-9
|View full text |Cite
|
Sign up to set email alerts
|

Toward practical transparent verifiable and long-term reproducible research using Guix

Abstract: Reproducibility crisis urge scientists to promote transparency which allows peers to draw same conclusions after performing identical steps from hypothesis to results. Growing resources are developed to open the access to methods, data and source codes. Still, the computational environment, an interface between data and source code running analyses, is not addressed. Environments are usually described with software and library names associated with version labels or provided as an opaque container image. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Although regular software updates are overall a good thing, it poses a problem for future reproducibility. A researcher trying to reproduce a 10-year-old study in R v3.0 could have a headache, as they would need to roll back their R version, and possibly their operating system as well, as R and other languages require certain system dependencies for low-level routines [ 84 ].…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although regular software updates are overall a good thing, it poses a problem for future reproducibility. A researcher trying to reproduce a 10-year-old study in R v3.0 could have a headache, as they would need to roll back their R version, and possibly their operating system as well, as R and other languages require certain system dependencies for low-level routines [ 84 ].…”
Section: Recommendationsmentioning
confidence: 99%
“…Guix is described as a ‘functional package manager’ and has the unique benefit of giving bit-for-bit build reproducibility and verifiability [ 84 , 97 ]. This is a notable advantage, as Docker images are not verifiable nor guaranteed to build reproducibly in the future due to link decay.…”
Section: Recommendationsmentioning
confidence: 99%
“…Although regular software updates are overall a good thing, it poses a problem for future reproducibility. A researcher trying to reproduce a tenyear-old study in R v3.0 could have a headache, as they would need to roll back their R version, and possibly their operating system as well, as R and other languages require certain system dependencies for low-level routines [85].…”
Section: Compute Environment Controlmentioning
confidence: 99%
“…Guix is described as a "functional package manager" and has the unique benefit of giving bit-for-bit build reproducibility and verifiability [85,98]. This is a notable advantage, as Docker images are not verifiable nor guaranteed to build reproducibly in the future due to link decay.…”
Section: Compute Environment Controlmentioning
confidence: 99%
“…For algorithm configuration, pitfalls in empirical work have been previously identified (Bocchese et al 2018) and best practices to avoid them suggested (Eggensperger, Lindauer, and Hutter 2019). Recent initiatives on reproducible research focus on transparent research artifacts with Guix, a system that enables the building of computation environments (Vallet, Michonneau, and Tournier 2022). Software heritage projects aim at preserving source code and binaries from research software (Cosmo and Zacchiroli 2017;Audemard, Paulevé, and Simon 2020).…”
Section: Introductionmentioning
confidence: 99%